Expert elicitation of state shifts and divergent sensitivities to climate warming across northern ecosystems - Émilie Saulnier-Talbot; Éliane Duchesne; Dermot Antoniades; Dominique Arseneault; Christine Barnard; Dominique Berteaux; Najat Bhiry; Frédéric Bouchard; Stéphane Boudreau; Kevin Cazelles; Jérôme Comte; Madeleine-Zoé Corbeil-Robitaille; et al. (Communications Earth & Environment, 2024)
Abstract Northern regions are warming faster than the rest of the globe. It is difficult to predict ecosystem responses to warming because the thermal sensitivity of their biophysical components varies. Here, we present an analysis of the authors’ expert judgment regarding the sensitivity of six ecosystem components – permafrost, peatlands, lakes, snowpack, vegetation, and endothermic vertebrates – across northern landscapes ranging from boreal to polar biomes. We identified 28 discontinuous component states across a 3700 km latitudinal gradient in northeastern North America and quantified sensitivity as the transition time from an initial to a contrasting state following a theoretical step change increase in mean annual air temperature of 5 °C. We infer that multiple interconnected state shifts are likely to occur within a narrow subarctic latitudinal band at timescales of 10 to more than 100 years, and response times decrease with latitude. Response times differ between components and across latitudes, which is likely to impair the integrity of ecosystems.